Keefektifan bahan ajar berbasis praktikum sederhana untuk menurunkan miskonsepsi siswa pada materi sistem pencernaan makanan - Aulia, Hanna; Suhara, Suhara; Surakusumah, Wahyu (Assimilation: Indonesian Journal of Biology Education, 2020)
This study aims to determine the reduction of students' misconceptions on food digestive system material through simple practicum-based learning. Simple practicum that is carried out includes test of vitamin C content by titration of iodine and formalin test with turmeric. Simple practicum means using simple tools and materials that are easy to find and the operation is also easy. This research was conducted on high school class XI students in Bandung City as much as one class. The research method used was a weak experimental method. The sampling technique was carried out by purposive sampling. Decrease in student misconceptions in terms of the results of the pretest and posttest. After learning, a questionnaire is given to find out students' responses to simple practicum-based learning. The results of the study showed that simple practicum food test was able to reduce student misconceptions, with an average reduction in misconceptions by 72%. Students' misconceptions are seen based on the analysis of conceptual changes. Conceptual change type Pattern I is a change towards positive (understanding the concept) showing the highest percentage of 68%. The highest decrease in misconceptions was found in the concept of food substances, while the lowest decrease in misconception was found in the concept of structural and bioprocess relationships.